Critical Ecological Roles, Structural Attributes and Conservation of Old Growth Forest: Lessons From a Case Study of Australian Mountain Ash Forests - Lindenmayer, David; Bowd, Elle (Frontiers in Forests and Global Change, 2022)
Please see attached manuscript files to review abstract (as length is 1000 words it will not allow me to paste it into this submission system).